PROSEDUR PENYELESAIAN KENDALA PRAKTIK BALIK NAMA SERTIPIKAT DALAM PENGUASAAN HAK ATAS TANAH (STUDI PUTUSAN NOMOR 1/PDT.G/2024/PN NGB) - Viena Maysa; Hendriani Parwitasari (Media Bina Ilmiah, 2025)
To provide protection and guarantee legal certainty for the rights of its citizens - both individual and public rights - to land, the government has emphasized the importance of registering land rights. The UUPA mandates the government to carry out a land registration program as outlined in Article 19 of the UUPA. According to the provisions of government regulation number 24 of 1997, agreements involving the transfer of land rights, including the sale and purchase of land, should be carried out before the Land Deed Official (PPAT). However, in the case of decision number 1/Pdt.G/2024/PN Ngb, it is impossible to carry out a Deed of Sale and Purchase before the PPAT because the whereabouts of the certificate's owner are not known. The research method used in this research is normative juridical, which focuses on statutory regulations. In this article, we will discuss the legal consequences of buying and selling carried out under the hands and the status of land ownership for parties who have exercised physical control for more than 20 years as well as procedures for resolving obstacles to changing the name of a certificate based on court decision number 1/Pdt.G/2024/PN Ngb.